RBF neural networks for pattern classification - He, Jianlei. (2013)
Radial basis function neural networks (RBF neural networks), as an alternative to multilayer perceptions, have been found to be very advantageous to pattern recognition, machine learning and artificial intelligence. This thesis addresses the problem of RBF neural networks for pattern classification.